The Evaluation of Clinical Pathway Implementation on Cerebral Infarction in the Inpatient Care Unit of Bantul X Hospital - Duane Ayu Fitri; Sri Sundari (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
Stroke remains one of the major health problems, not only in Indonesia but also in the world. The improvement of stroke service process is expected to support better outcomes of stroke service quality. One of the clinical management uses is the implementation of clinical pathway (CP). The purpose of this study was to explore the implementation of clinical pathway cerebral infarction in the inpatient unit of Bantul X hospital. A convergent parallel mix-method design with case study approach. The quantitative sample is the patient’s total cerebral infarction medical record (June 2016-November 2016, n=27) and ICPAT checklist. Qualitative samples are doctors, nurses and people involved in the implementation of CP cerebral infarction obtained from deep interview with purposive sampling technique. The result of this study, ICPAT dimensio 1 (CP format) content and quality are good. Dimension 2 (CP documentation) moderate content and good quality. Dimension 3 (CP development) moderate content and good quality. Dimension 4 (CP implementation) content and quality are poor. Dimension 5 (CP maintenance) content and quality are moderate. Dimension 6 (role of organization) content and quality are good. Compliance rate of completeness of CP form is 22% and compliance of filling clinical pathway is 0 %. Most contraints due to busyness of the officer and time constraints. To improve the cerebral infarction CP implementation need more socialization, training, regular evaluation and full time facilitator.